TRENDS AND CHALLENGES OF PUPILS’ TRANSITION FROM PRIMARY TO JUNIOR SECONDARY SCHOOLS IN GOMBE STATE, NIGERIA - SULEIMAN, ZUBAIRU; HUSSAINI, HADIZA; SULAI, MARY ERASMUS; DUKKU, MUHAMMAD GURAMA (Sokoto Educational Review, 2022)
This study examined the trends and patterns of the transition rate of pupils in basic education in Gombe state over five years from 2014 to 2019. It adopted a mixed methods research design involving both quantitative and qualitative data with layers of population namely: basic education pupils, principals, head teachers, officials from the State Universal Basic Education Board (SUBEB), Local Government Education Authority (LGEA) and School Based Management Committee (SBMC) in the state. The research data collection was done through various instruments: official records, key informant interviews, a questionnaire and a focus group discussion. The data were analyzed using descriptive statistics of frequency and percentage, and a qualitative method of thematic analysis. The findings revealed that the transition of pupils during the period under review was on average about 59% owing to factors like costs of education, poverty and lack of interest in education among others. Hence, part of the recommendations made was that the Government of Gombe state should make a concerted effort towards eliminating all hidden costs attached to education at the basic level as well as making basic infrastructure available to attract and retain pupils throughout the stipulated 10 years of basic education as enshrined in the National Policy on Education in Nigeria.